Factors that influence the Healthy Transition to Retirement: Integrative Review - Rocha, Ana (2020)
Background: the reform involves an individual and social dimension, constituting a milestone in the development of the individual. Planning this transition is essential to improve satisfaction and quality of life. Objectives: identify the factors that facilitate the healthy transition to retirement. Methodology: the integrative review involved research in the search engines: CINAHL Complete; MEDLINE; Nursing & Allied Health Collection; Cochrane Central Register of Controlled Trials; Cochrane Methodology Register; Library, Information Science & Technology Abstracts and MedicLatina, having initially obtained 231 scientific productions that, after analysis according to the inclusion criteria, 7 articles were chosen. Results: the determining factors for the success of this transition are: age, gender, education, health, social network, lifestyle that precedes retirement, satisfaction with working life and financial condition. Health literacy and preparation for reform influences this transition, translating into the way beneficiaries face health, economic and social problems. Conclusion: preparing for reform in advance is essential. Developing programs to prepare for retirement, based on the personal project of the retired future, is crucial, translating into gains in health, greater well-being and quality of life.